Gemfibrozilo versus aceite de Sacha Inchi en la reducción de niveles de triglicéridos séricos en Rattus rattus var albinus - Vicuña Ríos, Augusto (2012)
Objective: To compare the triglyceride lowering effect of gemfibrozil against that of Sacha Inchi oil in Rattus rattus var albinus. Materials and Methods: Thirty-six animals were used. They were divided in two experimental groups (GE1 and GE2) and a control group (CG). The animals underwent a conditioning stage for two weeks, afterwards they were fed with fat-rich meals; and later, the animals from the two experimental groups received Sacha Inchi oil and gemfibrozil, respectively. Serum triglyceride levels were measured at the beginning of the trial, after receiving the fat-rich food and after one and two weeks receiving the test drugs. Results: Serum triglyceride levels had 45,57%, 44,83%, and 27,24% reductions in GE1, GE2 and CG groups, respectively, after two weeks receiving the test drugs. The mean difference of triglyceride values in GE1 and GE2 groups after one and two weeks receiving the test drugs was highly significant compared with values measured after receiving the fat-rich meals; and the difference between the experimental groups and the control group after two weeks using the test drugs was also significant, and the results obtained in the GE1 and GE2 groups were homogeneous (p= 0,600). Conclusion: Sacha Inchi oil showed a triglyceride lowering effect which was similar inefficacy to that of gemfibrozil in Rattus rattus var albinus, after one and two weeks using the test products.